Potential regulation of linoleic acid and volatile organic compound contents in meat of chickens by PLCD1 - Xiao-jing LIU; Yong-li WANG; Li LIU; Lu LIU; Gui-ping ZHAO; Jie WEN; Ya-xiong JIA; Huan-xian CUI (Journal of Integrative Agriculture, 2023)
Omega-3 (linolenic acid (ALA), docosapentaenoic acid, eicosapentaenoic acid) and omega-6 (linoleic acid (LA), arachidonic acid) polyunsaturated fatty acids are essential for health and normal physiological functioning in humans. Here we report a genome-wide association study (GWAS) on LA content in chicken meat. The 19 significant single nucleotide polymorphisms (SNPs) identified by the GWAS approach were annotated in VILL, PLCD1 and OXSR1 genes with highly polymorphic linkage blocks, and explained 4.5% of the phenotypic variation in the LA content. Specifically, the PLCD1 mRNA expression level was negatively correlated with the LA content, and significantly higher in chickens with low LA content than in those with high LA content. In addition, PLCD1 was found to be involved in metabolic pathways, etc. Furthermore, the LA content was correlated with volatile organic compounds (e.g., octanal, etc.), but no relationship was found with intramuscular fat and triglycerides in chicken meat. The results indicated that there are key SNPs in PLCD1 that regulate the content of LA, and it has no significant effect on fat deposition, but may affect the content of volatile organic compounds (VOCs).